Personality of Transformative Muslims by Buya Hamka - Dartim Ibnu Rushd (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2017)
This paper reviews the personal concept of transformative Muslims according to Buya Hamka. This topic is expected to contribute in the Islamic educational thought as an alternative of thought amid the educational problems in Indonesia. One of the problems that emerge today is the neglect of values and morals in each educational activity. By carrying out library research, this article revealed the concept propounded by Buya Hamka regarding with transformative Islamic education that should be emphasized on maximal efforts in fostering and strengthening the personality of transformative Muslims, resulting in changes toward more humanist, liberative and transformative attitudes and behaviors. Individual personality that includes the mind, soul, aspiration and physical figure should be developed comprehensively. Educational efforts in building a transformative Muslim personality can be carried out by practicing the activities of thinking and working. Therefore, the expectation of the benefits of preparing independent and responsible generations who are able to heed all the values and morals are attained.